The Problem of Plagiarism in Scientific Publications and Graduation Research Papers - V. I. Pleshchenko (Высшее образование в России)
The problem of mass plagiarism in scientific publications and qualification research papers is fairly acute in today’s Russia. Incorrect borrowings and  plagiarism have extended not only to scientific articles and dissertations, but  also to students’ courseworks and graduation research papers and diploma  thesis. The author has recently faced with a case of 100% plagiarism of his  article published in the Russian journal and in this paper describes the  possible practical steps to protect the author’s rights. In addition, the paper  analyzes the problems of scientific and publication ethics in the conditions of  rapid development of information and communication technologies, estimates factors of the paid publications market development  in Russia. The author points to the  information asymmetry leading to various forms of manipulation in academic  sphere including relations between laypersons and professional plagiarists.